2005
DOI: 10.1016/s1472-6483(10)61302-8
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric and perinatal outcome of 1655 ICSI and 3974 IVF singleton and 1102 ICSI and 2901 IVF twin births: a comparative analysis

Abstract: A total of 3974 IVF and 1655 ICSI singleton births and 2901 IVF and 1102 ICSI twin births were evaluated. Pregnancies after both fresh and frozen transfers were included. IVF and ICSI singleton pregnancies were very similar for most obstetric and perinatal variables. The only significant difference was a higher risk for prematurity (< 37 weeks of amenorrhoea) in IVF pregnancies compared with ICSI pregnancies (12.4 versus 9.2%, OR = 1.39, 95% CI = 1.15-1.70). For twin pregnancies, differences were not statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 48 publications
0
28
1
Order By: Relevance
“…Olivennes et al (1993) found no difference in the prevalence of (very) preterm birth and (very) low birthweight among 162 IVF and 263 COHS singletons, and Bonduelle et al (2002) also showed no differences among 1499 ICSI and 1556 IVF singletons. However, the analysis of Ombelet et al (2005) showed only a significantly higher risk of preterm birth among 3974 IVF singletons relative to 1655 ICSI singletons. The authors hypothesized that the indication for ICSI is predominantly a male factor.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Olivennes et al (1993) found no difference in the prevalence of (very) preterm birth and (very) low birthweight among 162 IVF and 263 COHS singletons, and Bonduelle et al (2002) also showed no differences among 1499 ICSI and 1556 IVF singletons. However, the analysis of Ombelet et al (2005) showed only a significantly higher risk of preterm birth among 3974 IVF singletons relative to 1655 ICSI singletons. The authors hypothesized that the indication for ICSI is predominantly a male factor.…”
Section: Discussionmentioning
confidence: 84%
“…Part of these data has been included in the Ombelet study. An explanation for the difference has not been offered by Ombelet et al (2005). In another study (Wang et al, 2002), preterm birth was significantly more often observed in the high-technology group [IVF, ICSI and gamete intra-Fallopian transfer (GIFT)] than in the low-technology group (IUI, donor insemination), with ORs of 2.39 and 1.50, respectively, compared with naturally conceived controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…137 When the perinatal and obstetrical variables are compared between ICSI and IVF, the results are very similar. 138 With respect to birth defects, Hansen et al 139 reported in 2002 that 9% of IVF babies had a birth defect versus 4.2% of non-IVF babies. The DOI:10.1002/MSJ odds ratio was 2.2 for both IVF and ICSI singletons.…”
Section: In Vitro Fertilization Outcomesmentioning
confidence: 99%
“…At the same time, the safety and possible complications of ART are still an open question. According to published reports, gestation abnormalities even in singleton induced pregnancy are more often detected than in spontaneous pregnancy [6][7][8]. Unfortunately, the structural and functional peculiarities of the placenta after ART are poorly studied.…”
mentioning
confidence: 99%